2011
DOI: 10.1002/hep.24006
|View full text |Cite
|
Sign up to set email alerts
|

Adipose triglyceride lipase is a major hepatic lipase that regulates triacylglycerol turnover and fatty acid signaling and partitioning

Abstract: Despite advances in our understanding of the ways in which nutrient oversupply and triacylglycerol (TAG) anabolism contribute to hepatic steatosis, little is known about the lipases responsible for regulating hepatic TAG turnover. Recent studies have identified adipose triglyceride lipase (ATGL) as a major lipase in adipose tissue, although its role in the liver is largely unknown. Thus, we tested the contribution of ATGL to hepatic lipid metabolism and signaling. Adenovirus-mediated knockdown of hepatic ATGL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
282
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(320 citation statements)
references
References 45 publications
35
282
3
Order By: Relevance
“…In the liver, the rate-controlling step in triglyceride breakdown is catalyzed by adipose triglyceride lipase (ATGL). 25,26 As previously shown for adipocytes, 27 insulin decreased ATGL expression in hepatocytes both at low (10 mM) or high (25 mM) glucose concentration (Figure 4a). Unexpectedly, PGE 2 also decreased ATGL expression.…”
Section: Pge 2 -Dependent Inhibition Of Lipolysis and Mitochondrial Bsupporting
confidence: 79%
“…In the liver, the rate-controlling step in triglyceride breakdown is catalyzed by adipose triglyceride lipase (ATGL). 25,26 As previously shown for adipocytes, 27 insulin decreased ATGL expression in hepatocytes both at low (10 mM) or high (25 mM) glucose concentration (Figure 4a). Unexpectedly, PGE 2 also decreased ATGL expression.…”
Section: Pge 2 -Dependent Inhibition Of Lipolysis and Mitochondrial Bsupporting
confidence: 79%
“…The present study clearly showed that three fibrates, fenofibrate, bezafibrate, and clofibric acid, reduced the hepatic concentration of TAG in dose-and time-dependent manners, although conflicting results appear in the literature concerning the effects of fenofibrate on hepatic TAG content (11,24). In the current study, fenofibrate behaved as the most powerful hepatic TAG suppressor, while clofibric acid was the least potent.…”
Section: Discussionsupporting
confidence: 41%
“…ATGL overexpression enhances TAG hydrolysis, and the consequential release of fatty acids drives PPARa activity in rat hepatocytes (11,14,45); conversely, ATGL deficiency leads to down-regulation of PPARa target genes in the liver (11). These findings strongly suggest that ATGL is critically involved in the hepatocellular mobilization of fatty acids and fatty acid signaling (45).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, hepatic depletion of adipose triglyceride lipase (ATGL) in mice leads to severe liver steatosis (Ong et al 2011). Decreased activity of ATGL in the liver of IR patients has also been associated with development of NAFLD (Kato et al 2008).…”
Section: Discussionmentioning
confidence: 99%